2016
DOI: 10.1007/s11661-016-3623-3
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up of High-Pressure Sliding (HPS) for Grain Refinement and Superplasticity

Abstract: The process of high-pressure sliding (HPS) is a method of severe plastic deformation developed recently for grain refinement of metallic materials under high pressure. The sample for HPS is used with a form of sheet or rod. In this study, an HPS facility with capacities of 500 tonnes for vertical pressing and of 500 and 300 tonnes for horizontal forward and backward pressings, respectively, was newly built and applied for grain refinement of a Mg alloy as AZ61, Al alloys such as Al-Mg-Sc, A2024 and A7075 alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 42 publications
8
29
0
1
Order By: Relevance
“…Here, the slope corresponds to m. Particularly, in the superplastic regions (EL > 400% at the temperature range of 250350°C), the m values result in the range of 0.30.4. These m values are fairly comparable to 0.5 expected from the rate-controlling mechanism based on grain boundary sliding (GBS), 16) and in fact several studies reported the m values of 0.30.4 for the superplasticity at higher temperatures. 3641) The occurrence of GBS is verified from the SEM observation as in Fig.…”
Section: Sem Topographysupporting
confidence: 78%
See 4 more Smart Citations
“…Here, the slope corresponds to m. Particularly, in the superplastic regions (EL > 400% at the temperature range of 250350°C), the m values result in the range of 0.30.4. These m values are fairly comparable to 0.5 expected from the rate-controlling mechanism based on grain boundary sliding (GBS), 16) and in fact several studies reported the m values of 0.30.4 for the superplasticity at higher temperatures. 3641) The occurrence of GBS is verified from the SEM observation as in Fig.…”
Section: Sem Topographysupporting
confidence: 78%
“…It is thus demonstrated that the HPT process can introduce the advent of HSRS and LTSP in the A7075 alloy. 3.4.2 Strain rate sensitivity (m) and activation energy (Q) High-temperature deformation can be described by the following constitutive equation 16) and it is useful to understand the deformation mechanism for the deformation.…”
Section: Sem Topographymentioning
confidence: 99%
See 3 more Smart Citations